Giant Cell Arteritis Presenting as Scalp Necrosis - Daniel E. Maidana; Silvia Muñoz; Xènia Acebes; Roger Llatjós; Anna Jucglà; Alba Álvarez (The Scientific World Journal)
The differential of scalp ulceration in older patients should include several causes, such as herpes zoster, irritant contact dermatitis, ulcerated skin tumors, postirradiation ulcers, microbial infections, pyoderma gangrenosum, and giant cell arteritis. Scalp necrosis associated with giant cell arteritis was first described in the 1940s. The presence of this dermatological sign within giant cell arteritis represents a severity marker of this disease, with a higher mean age at diagnosis, an elevated risk of vision loss and tongue gangrene, as well as overall higher mortality rates, in comparison to patients not presenting this manifestation. Even though scalp necrosis due to giant cell arteritis is exceptional, a high level of suspicion must be held for this clinical finding, in order to initiate prompt and proper treatment and avoid blindness.